1989
DOI: 10.1080/00021369.1989.10869714
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aggregation of Cod (Gadus morhua) Muscle Proteins Using l-Ethyl-3-(3-Dimethylaminopropyl) Carbodiimide as a Zero Length Cross-linker

Abstract: The initial stages of thermally-induced aggregation of cod myofibrils resulted from noncovalent intermolecular cross-linking as demonstrated by SDS electrophoresis. The nature of the noncovalent bonds was studied by introducing a zero length cross-linker, l-ethyl-3-(3-dimethylamino propyl) carbodiimide (EDC). This allowed the examination of the noncovalent interactions by SDS electrophoresis and quantitative densitometry. Initially, during heating, about 50% of the myosin heavy chain was cross-linked to form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…70 °C. This may confirm that the aggregation of protein precedes its gelation and is related to different interactions of a part of the myosin tail and head regions [ 42 ]. Chan et al [ 43 ] indicated that the aggregation rate of fish myosin through non-covalent bonds increased rapidly at temperatures between 32 and 50 °C.…”
Section: Resultsmentioning
confidence: 66%
“…70 °C. This may confirm that the aggregation of protein precedes its gelation and is related to different interactions of a part of the myosin tail and head regions [ 42 ]. Chan et al [ 43 ] indicated that the aggregation rate of fish myosin through non-covalent bonds increased rapidly at temperatures between 32 and 50 °C.…”
Section: Resultsmentioning
confidence: 66%
“…During heating a suspension of cod myofibrillar protein, Gill and Conway (1989) observed initiation of its aggregation at 40 °C. They found that actin, along with other low‐ molecular‐weight species, only became involved in the polymerizing process through hydrophobic interactions once half of the myosin heavy chain (MHC) molecules were cross‐linked.…”
Section: Myofibrillar Protein Fractionsmentioning
confidence: 99%
“…The elasticity of the final gels decreased with higher levels of F-actin, leading the latter researchers to propose that F-actin was responsible for the viscous element of the system. During heating a suspension of cod myofibrillar protein, Gill and Conway (1989) observed initiation of its aggregation at 40 • C. They found that actin, along with other low-molecular-weight species, only became involved in the polymerizing process through hydrophobic interactions once half of the myosin heavy chain (MHC) molecules were cross-linked. This would imply that although interacting with myosin, F-actin does not play a role in establishing the protein network (Stone and Stanley 1992).…”
Section: Referencesmentioning
confidence: 99%
“…Meanwhile, as the temperature increased above 60 ℃, the amount of hydrophobic interactions increased as more hydrophobic groups were gradually exposed. The increase in hydrophobic interactions appeared to be involved in the formation of the gel (Gill and Conway, 2014; Shigeru and Shuryo, 1985). Hydrophobic interactions are thus considered to be the most important mechanism in the formation of minced fish gel during the heating process (Hayakawa and Nakai, 1985).…”
Section: Resultsmentioning
confidence: 99%